High Capacity of Nutrient Accumulation by Invasive Solidago canadensis in a Coastal Grassland - Ye, Xiao-Qi; Yan, Ya-Nan; Wu, Ming; Yu, Fei-hai (Frontiers in Plant Science, 2019)
Background: Solidago canadensis is a notorious invasive species from North America that is spreading across East China. It is invading some coastal grasslands and replacing native grass species. The effects of the S. canadensis invasion on soil nutrient cycling in the grasslands remain unclear. This study examined the effects of the invasion of S. canadensis on macronutrient accumulation in species aboveground part and soil. Methods: Aboveground biomass, macronutrient (N, P and K) pools in biomass, litter mass and decomposition rates, soil macronutrient availability and soil microbial biomass and enzyme activity that were related to nutrient transformation were compared between plots invaded by S. canadensis and uninvaded plots dominated by three different native grass species: Phacelurus latifolius, Phragmites australis and Imperata cylindrica. Results: S. canadensis had higher aboveground biomass, higher leaf N, P and K concentrations, and consequently, a larger macronutrient pool size in the standing biomass. S. canadensis also produced more litter with higher N, P and K concentrations and faster decomposition rates. The S. canadensis invasion did not change the total N, P and K concentration in the topsoil (0-10 cm), but the invasion did increase their availability. The S. canadensis invasion did not increase the total soil organic matter content but did increase the soil microbial biomass and the activities of urease, alkaline phosphatase, invertase, amylase and glucosidase in the topsoil. Conclusions: The invasion of S. canadensis accelerates the macronutrient cycling rate via increases in aboveground productivity and nutrient accumulation in standing biomass, faster nutrient release from litter and higher soil microbial activity. An enhanced nutrient cycling rate may further enhance its invasiveness through a positive feedback on soil processes.